Franco at Bilbao (extract) - Appelius, Mario, 1892-1946
1939-06-20 012b-0027-005 -4- At the propitious moment it mobilised even the Jewish bankers, dangling before the eyes of the business men in Bilbao the attractive prospect of a huge English loan for strengthening their industry. The undeniable economic injury suffered by the population of Biscay as a result of the suppression of the fiscal secular privilege constituted, according to London, the spiritual and material basis of an enduring tacit resistance of the Basque people to Franco. London hoped to manipulate that resistance. England is tenacious and its hold is not soft when it is a question of British economic interests. The great imperial history of England is made up of hundreds of similar stories, the brutality and injustice of which are accepted by the British conscience, provided they bear the seal of London. The enthusiastic reception accorded during the last few days by the inhabitants of Bilbao, Biscay and Guipúzcoa, to the Caudillo of the new Spain, one, great and free, has therefore, a special significance as an index of the new internal political situation in Spain, and as an eloquent reminder of the acceptance by the population of the new Spanish foreign policy which, as is well known, is a policy of imperial independence and economic autarchy. Franco's presence in Bilbao signifies that henceforward the iron of Biscay will serve the political and economic interests of Spain and no longer the industrial and financial calculations of the City. Henceforward, Biscay will be free to create such industries as Spain may consider expedient and necessary for the life of the Nation, without further asking the approval of the omnipotent City. From the Baltic to the Red Sea, from Bilbao to Tientsin, England is gradually losing its imperial arteries through which it egoistically pumped the riches of the world. The radiant days of Bilbao, overflowing with imperious good will, prove two points: 1, Basque separatism, like Catalan separtism, has now received a death-blow. The Basques, like the Catalans, have accepted the conception of that totalitarian union of Spain which is one of the great directing policies of Franco: 2. The imperial programme of independence and autarchy of the new Spain finds enthusiastic support even in zones which, like Biscay, have considered themselves for half a century as the economic and financial offshoots of London: 3. England has lost in the Basque "footstool" its principal instrument of spiritual and political domination over Madrid. 292/946/12b/28(iv)